Research Recommendations Following the Discovery of Pain Sensitizing IgG Autoantibodies in Fibromyalgia Syndrome. Issue 6 (26th November 2021) - Goebel, Andreas; Andersson, David; Barker, Chris; Basu, Neil; Bullock, Craig; Bevan, Stuart; Bashford-Rogers, Rachael J M; Choy, Ernest; Clauw, David; Dulake, Debra; Dulake, Richard; Flor, Herta; et al.
Abstract: Background: Fibromyalgia syndrome (FMS) is the most common chronic widespread pain condition in rheumatology. Until recently, no clear pathophysiological mechanism for fibromyalgia had been established, resulting in management challenges. Recent research has indicated that serum immunoglobulin Gs (IgGs) may play a role in FMS. We undertook a research prioritisation exercise to identify the most pertinent research approaches that may lead to clinically implementable outputs. Methods: Research priority setting was conducted in five phases: situation analysis; design; expert group consultation; interim recommendations; consultation and revision. A dialogue model was used, and an international multi-stakeholder expert group was invited. Clinical, patient, industry, funder, and scientific expertise was represented throughout. Recommendation-consensus was determined via a voluntary closed eSurvey. Reporting guideline for priority setting of health research were employed to support implementation and maximise impact. Results: Arising from the expert group consultation (n = 29 participants), 39 interim recommendations were defined. A response rate of 81.5% was achieved in the consensus survey. Six recommendations were identified as high priority- and 15 as medium level priority. The recommendations range from aspects of fibromyalgia features that should be considered in future autoantibody research, to specific immunological investigations, suggestions for trial design in FMS, and therapeutic interventions that should be assessed in trials. Conclusions: By applying the principles of strategic priority setting we directed research towards that which is implementable, thereby expediating the benefit to the FMS patient population. These recommendations are intended for patients, international professionals and grant-giving bodies concerned with research into causes and management of patients with fibromyalgia syndrome.